2021
DOI: 10.1021/jacs.1c11791
|View full text |Cite
|
Sign up to set email alerts
|

Epoxide Electroreduction

Abstract: Selective hydrogenation of epoxides would be a direct and powerful approach for alcohol synthesis, but it has proven to be elusive. Here, electrochemically epoxide hydrogenation using electrons and protons as reductants is reported. A wide range of primary, secondary, and tertiary alcohols can be achieved through selective Markovnikov or anti-Markovnikov ring opening in the absence of transition metals. Mechanistic investigations revealed that the regioselectivity is controlled by the thermodynamic stabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 61 publications
0
51
0
1
Order By: Relevance
“…The formation of racemic product 2 s supported the participation of benzyl radical intermediates in this reaction (Scheme 3, c). [16] The cyclopropyl substituted epoxide 1 q did not undergo a radical clock ring-opening reaction under standard conditions, which probably suggested that the formed carboxylated radical intermediates were rapidly transformed into carbanion intermediates through another electron transfer process. When D 2 O was introduced into the reaction of 1 a, α-deuterated alcohol 14 was isolated in 25 % yield with 90 % deuterium incorporation, suggesting the formation of αcarbanion intermediates in the reaction ( Scheme 3,d).…”
Section: Methodsmentioning
confidence: 99%
“…The formation of racemic product 2 s supported the participation of benzyl radical intermediates in this reaction (Scheme 3, c). [16] The cyclopropyl substituted epoxide 1 q did not undergo a radical clock ring-opening reaction under standard conditions, which probably suggested that the formed carboxylated radical intermediates were rapidly transformed into carbanion intermediates through another electron transfer process. When D 2 O was introduced into the reaction of 1 a, α-deuterated alcohol 14 was isolated in 25 % yield with 90 % deuterium incorporation, suggesting the formation of αcarbanion intermediates in the reaction ( Scheme 3,d).…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, the groups of Qi and Lu have reported electrochemical hydrogenation of epoxides to alcohols using electrons and protons as reducants (Scheme 18d). [40] According to their mechanistic studies, aryl substituted epoxides resulted in anti-Markovnikov linear alcohols in which the selectivity was controlled by the high stability of the in situ generated benzyl radicals. Aliphatic alkyl epoxides provided kinetically favored secondary alcohols selectively.…”
Section: Reductants Other Than Hydrogenmentioning
confidence: 99%
“…Numerous terminal and internal epoxides were hydrogenated into the corresponding anti ‐Markovnikov alcohols in moderate to good yields. Very recently, the groups of Qi and Lu have reported electrochemical hydrogenation of epoxides to alcohols using electrons and protons as reducants (Scheme 18d) [40] . According to their mechanistic studies, aryl substituted epoxides resulted in anti ‐Markovnikov linear alcohols in which the selectivity was controlled by the high stability of the in situ generated benzyl radicals.…”
Section: Reductants Other Than Hydrogenmentioning
confidence: 99%
“…In recent years, electrochemical synthesis has received increasing attention for its powerful ability to forge chemical bonds, presumably due to the advantages of no external stoichiometric chemical oxidants or reductants and milder conditions over the conventional approaches [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. As a result, we speculate that electrochemistry maybe provides a unique opportunity to facilitate the functionalization of azobenzene.…”
Section: Introductionmentioning
confidence: 99%